A curious case of COVID-19 and “empyema” - Kurian, Elizabeth; Joseph, Jijo; Mukundan, Anjali N.; Anand, Rajeev (International Journal of Advances in Medicine, 2021)
The coronavirus disease -19 (COVID-19) pandemic has challenged the existing healthcare systems in many ways. The varied presentations and numerous complications described is one of the most pressing concerns of the ongoing pandemic. Here we present an unusual case which was initially misdiagnosed due to presence of coexisting corona virus infection